High temperature creep resistance of a thermally stable nanocrystalline Fe-5 at.% Zr steel. (1st April 2020) - Shan, G.B.; Chen, Y.Z.; Li, Y.J.; Zhang, C.Y.; Dong, H.; Cong, Y.B.; Zhang, W.X.; Huang, L.K.; Suo, T.; Liu, F.
Abstract: The application of nanocrystalline (NC) materials at high temperatures is challenging due to their poor thermal stability or low creep resistance. Here we report that a thermally stable NC Fe-5 at.% Zr steel produced by High-Pressure-Thermal-Compression sintering exhibits an excellent creep resistance (with a creep rate of 3.92 × 10 −8 s −1 at 923 K and under the applied stress of 250 MPa). The excellent creep resistance is ascribed to its highly stable NC structure stabilized by nano-sized precipitates. Mechanical testing suggests that the creep of the NC Fe-5 at.% Zr steel is controlled by dislocation activities rather than diffusion dominated mechanisms. Graphical abstract: Image, graphical abstract